2013 International Conference on Informatics and Creative Multimedia 2013
DOI: 10.1109/icicm.2013.10
|View full text |Cite
|
Sign up to set email alerts
|

A Conceptual Model of Interactive Persuasive Learning System for Elderly to Encourage Computer-Based Learning Process

Abstract: Over the past few years, new and improved learning techniques and technologies have been introduced. Among them, interactive media holds a lot of potential in learning. This technology highly promotes self-directed and active learning approaches and has capabilities to foster the learning process. Furthermore, the emergence of persuasive technology increased the capability of the media features to be used in learning field within variety of ways. Persuasive technology is the attempts of several researchers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Students must be more creative and have high imagination in illustrating so that they can understand what is being learned by visualizing them in their mind [59,60]. This learning area is based on the level of student's thinking on how they can become with high productivity in their work, with a high level of cognitive thinking for increasing their learning environment.…”
Section: Elements Of Interactive Learningmentioning
confidence: 99%
“…Students must be more creative and have high imagination in illustrating so that they can understand what is being learned by visualizing them in their mind [59,60]. This learning area is based on the level of student's thinking on how they can become with high productivity in their work, with a high level of cognitive thinking for increasing their learning environment.…”
Section: Elements Of Interactive Learningmentioning
confidence: 99%
“…It supports the researcher to decide the relationship among those components in enhancing the understanding of the research problem and solution (Zulkifli et al, 2013). The conceptual model is a huge asset in a research study because through the use of the model, researcher, designer and developer are able to visualize a project from their perspective (Zulkifli et al, 2013).…”
Section: The Estar Conceptual Modelmentioning
confidence: 99%
“…It supports the researcher to decide the relationship among those components in enhancing the understanding of the research problem and solution (Zulkifli et al, 2013). The conceptual model is a huge asset in a research study because through the use of the model, researcher, designer and developer are able to visualize a project from their perspective (Zulkifli et al, 2013). Several important models, theories and principles have been employed namely; the ARCS (Attention, Relevance, Confident and Satisfaction), the Cognitive Theory of Multimedia Learning (CTML), the Intrinsic Motivation Theory and Multimedia Learning Principles.…”
Section: The Estar Conceptual Modelmentioning
confidence: 99%
“…However, 1.3. Motivation, Objective and Rationale the design and implementation of persuasive (learning) technology are complex tasks since it is hard to estimate the effectiveness of those strategies regarding each learner (GRAM-HANSEN;SCHÄRFE;DINESEN, 2012;ZULKIFLI et al, 2013). For instance, many efforts of the research community have shown the weakness of one-size-fits-all approach to tackle motivation in persuasive technology.…”
Section: Motivation Objective and Rationalementioning
confidence: 99%
“…Yet, trying to figure out what is the right message for a student and how to deliver it at the right time are still difficult tasks. As shown in (GRAM-HANSEN; SCHÄRFE; DINESEN, 2012) and (ZULKIFLI et al, 2013), the design and implementation of persuasive systems (e.g., persuasive learning systems) are complex tasks since it is hard to estimate the effectiveness of those strategies regarding each learner. One promising way to improve the effectiveness of technology-based persuasive interventions relies on the design of personalized persuasive principles (i.e., backed up by social psychology theory) and tailored to fit user's personality traits.…”
Section: Persuasion Profilingmentioning
confidence: 99%